Hebrew wordplay and Septuagint translation technique in the fourth book of the Psalter - Backfish, Elizabeth H. P. (Library of Hebrew Bible/Old Testament studies, 2019)
"This volume examines numerous Hebrew wordplays not identified and discussed in previous research, and the technique of the Septuagint translators, by offering another criterion of evaluation - essentially, their concern about the style of translating Hebrew into Greek. Elizabeth Backfish's study analyzes seventy-four wordplays employed by the Hebrew poets of Psalms 90-106, and how the Septuagint renders Hebrew wordplay in Greek. Backfish estimates that the Septuagint translators were able to render 31% of the Hebrew semantic and phonetic wordplays (twenty-four total), most of which required some sort of transformation, or change, to the text in order to function in Greek. After providing a thorough summary of research methods on wordplay, definitions and research methodology, Backfish summarizes all examples of wordplay within the Fourth Psalter, and concludes with examples of the wordplay's replication, similar rendition or textual variation in the Septuagint. Emphasising the creativity and ingenuity of the Septuagint translators' work in passages that commentators often too quickly identify as the results of scribal error or a variant Vorlage from the Masoretic text, Backfish shows how the aptitude and flexibility displayed in the translation technique also contributes to conversations in modern translation studies."--Bloomsbury Publishing.